Career Development Theories for the Education of Unemployed - Stalidzāne, Gita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The topicality of the research – To determine the tendencies of the development of career services, conclusions of career theories have been analysed in the article, the career promoting and hindering factors in the State Employment Agency have been investigated, which could help to employ the forms, methods and techniques of pedagogical organization thus creating preconditions for a more successful career development of the clients.The aim of the research – to explore the career theories, which can be used for the unemployed to obtain their education or to improve their motivation according to the economic situation. Career development theories such as career development structural or opportunity theories (J.Klimov, J.Parson, J.Holland, K.G.Jung)  and development or lifespan theories (D.Super, L.Ginsberg, R.Havighurst, E.Erikson, J.Krumbolz, A.Bandura, Dh.Fukuyama) were investigated. In the changing conditions of economics new requirements for the working people are being developed because of formation of new forms of employment. The former advantage in Latvia – the relevantly cheap labour force, has already ceased to exist, so in the future it will not be able to serve as the resource for the economical development. In the formation of an educated society only purposeful educational action can ensure the development and prosperity of the state, so enabling the individuals to find creative solutions in critical situations and adapt in a new environment. The main problem is the contradiction between the acquisition of the value of education in the adult society and the fact that the unemployed in adult age have the lack of knowledge for making their career. Everybody has a different career, it is developing dynamically all through the lifetime. The career reflects the skill of the individual to find balance between the salaried work and the unpaid work, as well as the duties of the personal life.